Effect of alkaline treatment on the thermo-physicochemical and mechanical properties of biochar powder/Washingtonia robusta fibers/PLA hybrid biocomposites - Dembri, Isma; Belaadi, Ahmed; Lekrine, Abdelaziz; Jawaid, Mohammad; Ismail, Ahmad Safwan; Ghernaout, Djamel (Elsevier, 2024)
Replacing plastic products with fully biodegradable products remains a challenge in our daily lives. Biodegradable hybrid bio composites are designed for various structural and non-structural applications such as car interiors, filaments for 3D printers, biomedical, sports and electronic products, green building materials and food packaging. In this work hybrid composites fabricated using polylactic acid (PLA) matrix reinforced with short plant fibers from the Washingtonia robusta (WR) palm tree and biochar powder (BC) with grain diameters less than 0.6 μm obtained from WR palm waste after carbonization at 300 °C. Initially, a portion of the untreated plant fibers was retained, while the other portion was treated with NaOH (1, 2, 3%) for 15 h. Indeed, the untreated and alkali-treated fibers were observed by SEM and then characterized by thermogravimetric analysis/differential scanning calorimetry. Fourier transform infrared showed physical and chemical changes with surface degradation of the WR treated at higher concentrations (3% NaOH). In addition, establish the relationship between the alkali treatments of the biocomposite reinforcement fibers and the improvement of the mechanical performance of these materials. The best results obtained for the developed biocomposite hybrid products are those of BTR3, for mechanical characteristics such as traction, flexural strength and Izod, with values of 39.56 MPa and 74.43 MPa, and 3.26 kJ/m2 respectively; and 2.30 MPa as elastic stress, also for water absorption with a percentage of 8.3%. The percentages of the alkaline treatments used revealed that the BTR3 model presents the best physical-chemical and mechanical behavior of these new materials.